Big trees, small favors: loggers and communities in Amazonia - Medina, G.; Shanley, P. (2004)
This article explores the changing livelihoods and resource management choices of three rural communities in a dynamic logging frontier region along the Capim River in the eastern Amazonian State of Pará, Brazil. A study of 13 successive logging events during a twenty-year time span in a 3,000 ha community forest demonstrated that the relationship between loggers and communities is a highly ambiguous one changing over time from compatible to conflictive. Over the course of a decade, communities began to experience loss of fruit, medicinal and game attracting species with high value to their daily livelihoods, yet they never faltered from selling their timber rights. Two socioeconomic factors were identified which influenced communities to sell timber despite the losses in non-timber forest products: paternalistic relationships among buyers and community members and expanding market involvement requiring more cash to meet increasing needs.